Revealing the Complete Chloroplast Genome of an Andean Horticultural Crop, Sweet Cucumber (Solanum muricatum), and Its Comparison with Other Solanaceae Species - Saldaña Serrano, Carla Lizet (2022)
Sweet cucumber (Solanum muricatum) sect. Basarthrum is a neglected horticultural crop native of the Andean region. It is naturally distributed very close to other two Solanum crops of high importance, potatoes and tomatoes. To date, molecular tools for this crop are still undetermined. In this study, the complete sweet cucumber chloroplast (cp) genome was obtained and compared with seven Solanaceae species. The cp genome of S. muricatum had a 155,681 bp in length with included a large single copy (LSC) region of 86,182 bp and a small single-copy (SSC) region of 18,360 bp, separated by a pair of inverted repeats (IR) regions of 25,568 bp. The cp genome possessed 88 protein-coding genes (CDS), 37 transfer RNA (tRNA) genes, eight ribosomal RNA (rRNA) genes, and one pseudogene. Furthermore, 48 perfect microsatellites were identified, divided in mononucleotide repeats (32), followed by tetranucleotide (6) and dinucleotides (5). Microsatellites with trinucleotides repeats (3), pentanucleotide (1) and hexanucleotide (1) repeats motifs in these genomes were also identified, but in lower quantity. These repeats were mainly located in the noncoding regions. Whole cp genome comparative analysis revealed that the SSC and LSC regions showed more divergence than IR regions. Our phylogenetic analysis showed that S. muricatum is a sister species to members of sections Petota + Lycopersicum + Etuberosum. We expect to provide useful molecular data to shed light on the genetic diversity within sweet cucumber landrace, and also to determine the evolutionary processes in S. muricatum.